The biggest damned hat: tales from territorial Alaska lawyers and judges - Cravez, Pamela, author; University of Alaska Press, publisher (Colorado State University. Libraries, 2017)
Alaska history from the days before statehood is rich in stories of colorful characters--prospectors, settlers, heroes, and criminals. And right alongside them were judges and lawyers, working first to establish the rule of law in the territory, then, later, laying the groundwork for statehood. [This book is a] collection of stories ranging from the gold rush to the 1950s. Built on interviews and oral histories from more than fifty lawyers who worked in Alaska before 1959, and buttressed by research into legal history, the book offers a ... portrait of law in the territory--from laying the groundwork for strong civil and criminal law to helping to secure mining and fishing rights to the Alaska Court-Bar fight, which pitted Alaska's community of lawyers against its nascent Supreme Court. Bringing to life a time long past--when some of the best lawyers had little formal legal education--[this book] fills ... a part of the story of Alaska's history.--Provided by publisher.
Introduction -- Three lucky Swedes and one corrupt judge -- Wickersham chafes under Eagle's slow pace -- George Grigsby's biggest damned hat -- Becoming Norman Banfield -- W.C. Arnold: territorial Alaska's most powerful lobbyist -- Mildred Hermann and Dorothy Haaland: independent thinking women -- Hellenthal chooses Anchorage -- Tales of the silver fox -- Judge George Folta: license to hunt -- Remembering Judge Folta and Ketchikan's red light district -- Influence and discipline: policing territorial lawyers -- Buell Nesbett: navigating territorial waters and getting soaked -- Anchorage lawyers: creating a better system -- Rocky seas: the great Alaska court-bar fight -- Nesbett's surrogate -- Grace Berg Schaible and the Tanana Valley bar -- More frontier stories -- Afterword.
Keywords: Law -- Alaska -- History; Lawyers -- Alaska -- Biography; Law -- Alaska -- Anecdotes; Alaska -- History -- 1867-1959